Judi Online Pemicu Keretakan Rumah Tangga (Studi Kasus Pengadilan Agama Sangatta) - Evi Marpiah; Hartono; Mukhtar (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
Divorce due to online gambling is a phenomenon that has increased in recent years. Based on research at the Sangatta Religious Court, online gambling can trigger household breakdown. This research uses a descriptive method with a qualitative approach used to understand and explain social phenomena in depth and detail. Data was collected through observation, interview and documentation techniques from related sources. The results showed that the causes of someone falling into online gambling are due to invitations, curiosity, and economic problems are also a cause because some people are still in the category of low-income people so they are unable to meet their daily needs. The impact of online gambling triggers prolonged conflict and can lead to divorce or separation. In addition, the emotional distress caused by online gambling affects the quality of communication and reduces the level of household happiness. Thus, awareness and prevention efforts are needed from various parties to minimize the negative impact of online gambling in order to maintain household harmony.